2023
DOI: 10.3389/fgene.2023.1101612
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis reveals the landscape of immune cell infiltration and novel immune-related biomarkers in moyamoya disease

Abstract: Objective: This study aimed to identify immune infiltration characteristics and new immunological diagnostic biomarkers in the cerebrovascular tissue of moyamoya disease (MMD) using bioinformatics analysis.Methods: GSE189993 and GSE141022 were downloaded from the GEO database. Differentially expressed gene and PPI analysis were performed. After performing WGCNA, the most significant module associated with MMD was obtained. Next, functional pathways according to GSEA, GO, and KEGG were enriched for the aforemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…In the present study, STK3 also showed a positive correlation with neutrophils. In addition, some studies have compared a variety of immune cells in patients with moyamoya disease and normal controls 39 . Among them, macrophages and mesenchymatous granulocytes were up-regulated in moyamoya disease, which was consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, STK3 also showed a positive correlation with neutrophils. In addition, some studies have compared a variety of immune cells in patients with moyamoya disease and normal controls 39 . Among them, macrophages and mesenchymatous granulocytes were up-regulated in moyamoya disease, which was consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%